Studi Literatur: Peranan Teknik Audit Investigasi Dan Profesionalisme Auditor Investigasi Untuk Mengetahui Tingkat Kecurangan (Fraud) - Suci Nurlayli Alimatu Sholiqah; Tri Ratnawati (Jurnal Akuntan Publik, 2024)
This research aims to determine the role of investigation audit techniques, investigative audit standards and investigative audit profesionalism in determining the level of fraud. There have been many fraud cases that have occured, especially in Indonesia, so we need to know the magnitude of the influence of each variable in knowing and disclosing the level of fraud that has occurred. Audit techniques and standards that are applied optimally, complemented by high professionalism of auditors, should produce maximum results in revealing and knowing the level of fraud that has occurred. This research uses qualitative methods by conducting literature studies from previous articles and research. Data sources were obtained from journals, books and articles on the internet that were relevant to the theme of this research. The result of this researchs are that investigative audit techniques and the proffesionalism of investigative auditors have an influence in disclosing fraud to determine the level of fraud that has occurred.